Adenoid cystic carcinoma in an 86-year-old male patient: A rare case report - Rim Alami, MD; Reyzane El Mjabber, MD; Malak Chahid, MD; Meryem Naciri, MD; Zineb Dahbi, MD; Fadila Kouhen, MD; Sanaa El Majjaoui, MD; Nabil Ismaili, MD; Asmaa Naim, MD, PhD (Radiology Case Reports, 2025)
Adenoid cystic carcinoma (ACC) is characterized by slow growth, a marked tendency for local invasion, and a high rate of recurrence. In this context, we present a noteworthy case of ACC in an 86-year-old North African male, arising in the retromolar trigone-an exceptionally rare location. This case report outlines the clinical presentation, diagnostic workup, therapeutic interventions, and patient outcomes associated with ACC, highlighting the complexities inherent in the management of this challenging malignancy. Our findings emphasize the critical role of multidisciplinary collaboration, ongoing research, and individualized treatment strategies to optimize ACC management and enhance patient care.